Investigation of the Intestinal Permeability of Ciclosporin Using the in situ Technique in Rats and the Relevance of P-Glycoprotein - Zakeri-Milani, Parvin; Valizadeh, Hadi; Islambulchilar, Ziba; Damani, Sanaz; Mehtari, Maryam (Arzneimittelforschung, 2008)
The primary endpoint of this study was to determine the intestinal permeability of Ciclosporin (cyclosporine A, CsA, CAS 59865-13-3) using the single-pass intestinal perfusion technique (SPIP) and a range of concentrations in rats. The second objective was to assess the quantitative contribution of P-glycoprotein (P-gp) -mediated efflux in limiting the oral bioavailability of CsA using erythromycin (Ery, CAS 114-07-8) as an inhibitor of P-gp efflux transporter. A solution containing CsA and phenol red either in the presence or in the absence of Ery as a P-gp inhibitor was perfused through a cannulated jejunal segment in rats. Outlet samples were collected every 10 min in micro tubes up to 90 min. Samples were analyzed using a modified reverse phase HPLC method. The mean effective permeability coefficients (Peff ) of CsA in concentrations of 5,10,15 and 20 µmol/L in the perfusion solution were found to be 2.21 (± 0.26) × 10–4 cm/s, 3.34 (± 1.29) × l0–4 cm/s, 3.12 (± 0.23) x 10–4 cm/s and 2.73 (± 0.28) × 10–4 cm/s, respectively. The corresponding values in the presence of Ery were found to be 3.96 (± 1.04) × 10–4 cm/s, 5.34 (± 1.29) × 10–4 cm/s, 3.72 (± 0.21) × 10–4 cm/s and 4.41 (± 0.89) × 10–4 cm/s, respectively.The two-tailed Student’s t-test showed that the intestinal permeability of CsA was significantly increased by Ery in all four CsA concentrations used (P < 0.05). However, there was no significant difference between the Peff values of CsA in different concentrations, indicating that the CsA permeation was independent of the concentration. Therefore it is concluded that at least some part of the observed clinical interaction between Ery and CsA is due to the interaction in absorption level.
Keywords: CAS 59865-13-3; Ciclosporin, intestinal permeability, rat; Immunosuppressants; P-glycoprotein